2014
DOI: 10.1186/1471-2164-15-695
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparison of microRNAs and their targeted transcripts among leaf, flower and fruit of sweet orange

Abstract: BackgroundIn plants, microRNAs (miRNAs) regulate gene expression mainly at the post-transcriptional level. Previous studies have demonstrated that miRNA-mediated gene silencing pathways play vital roles in plant development. Here, we used a high-throughput sequencing approach to characterize the miRNAs and their targeted transcripts in the leaf, flower and fruit of sweet orange.ResultsA total of 183 known miRNAs and 38 novel miRNAs were identified. An in-house script was used to identify all potential secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 63 publications
3
75
0
Order By: Relevance
“…miRNAs are small regulatory RNAs that play crucial roles in diverse aspects of plant development [54]. Identifying miRNA target genes is a fundamental step in determining the biological function for miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are small regulatory RNAs that play crucial roles in diverse aspects of plant development [54]. Identifying miRNA target genes is a fundamental step in determining the biological function for miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that miR164 is also involved in senescence of leaves in Arabidopsis [13,41]. In addition, interestingly, miR164 is one of the most abundant miRNAs in some fruits such as orange [42], grape [43,44], tomato [45], and prickly pear fruit (tuna) [46]. In orange, it was observed that miR164 has remarkably higher expression in fruits in comparison with other organs [42].…”
Section: Introductionmentioning
confidence: 89%
“…In addition, interestingly, miR164 is one of the most abundant miRNAs in some fruits such as orange [42], grape [43,44], tomato [45], and prickly pear fruit (tuna) [46]. In orange, it was observed that miR164 has remarkably higher expression in fruits in comparison with other organs [42]. Moreover, miR164 accumulates to high levels during fruit ripening [42,45,46].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other noteworthy miRNA candidates identified only in trichomes were miR-3954 which targets triose phosphate transporter gene required for metabolism and initiates siRNA biosynthesis [191][192][193] and miR-6483 which targets transmembrane proteins and regulates transport of cellular materials across the membrane 191,192,194 . To facilitate further studies of UMFA and AnAc synthesis in trichomes potential targets was uncovered.…”
Section: Identification Of Potential Physiological Roles Of Geranium mentioning
confidence: 99%